French guidelines for restrictive episiotomy during instrumental delivery were not followed by an increase in obstetric anal sphincter injury - Bertrand Gachon; Xavier Fritel; Olivier Rivière; Bruno Pereira; Françoise Vendittelli (Scientific Reports, 2022)
Abstract The objective was to assess the influence of the French guidelines in favor of a restrictive use of episiotomy on both episiotomy and obstetric anal sphincter injury (OASI) rates during instrumental delivery. It was aulticenter study involving 193 maternities between 2000 and 2016. We included women with a singleton pregnancy, with cephalic presentation at 34 weeks of gestation or more who underwent an instrumental delivery. The study period was divided into three phases: 2000–2005 (reference) 2006–2011, and 2012–2016. We calculated the adjusted relative risk (aRR) of episiotomy and OASI and investigated for changes in episiotomy and OASI rates over time by using Prais–Winsten regression. We considered 96,035 deliveries. The episiotomy’s risk was lower in 2006–2011 (69.4%) and 2012–2016 (59.1%) compared to 2000–2005 (81.2%), respectively: aRR 0.93 [0.92–0.95] and 0.89 [0.87–0.90]. The OASI’s risk was higher in 2006–2011 (2.5%) and 2012–2016 (3.1%) compared to 2000–2005, respectively: aRR 1.30 [1.10–1.53]) and 1.57 [1.33–1.85]. However, Prais–Winsten regression showed no difference in the OASI rate during the study period. We observed a massive decrease in episiotomy use and a moderate increase in crude OASI’s rate but multivariate analysis failed to report an association between these outcomes.